ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN STRES PADA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS MUHAMMADIYAH Jakarta - Aulia, Hardiman SG; Anggraeni (Health Safety Environment, 2025)
Background: Stress is a condition of anxiety or tension that arises due to challenging situations. According to the Indonesian National Adolescent Mental Health Survey (I-NAMHS), one in three Indonesian adolescents experiences mental health problems, while one in twenty suffers from mental disorders, covering approximately 15.5 million and 2.45 million adolescents, respectively. An initial observation conducted on students of the Faculty of Public Health (FKM) at the University of Muhammadiyah Jakarta (UMJ) revealed that 70% of students experience stress when working on final projects, course assignments, and organizational activities. This study aims to examine the relationship between stress and student characteristics at FKM UMJ. Methods: This study employs a quantitative analytic research method with a cross-sectional approach and uses the chi-square test to examine the relationship between student stress and variables such as age and gender. The study sample consists of 98 respondents selected using total sampling, covering the entire population of FKM UMJ students who meet the research criteria. Result: The results indicate no significant relationship between stress and age (p = 1.000) and gender (p = 2.267), both with p-values greater than 0.05. The majority of students experienced mild stress, with 63 out of 98 respondents reporting mild stress symptoms. Conclusion: This study shows that age and gender do not significantly relate to stress levels among students at the Faculty of Public Health, University of Muhammadiyah Jakarta. Further research is recommended to explore other factors that may influence student stress levels, such as academic workload or social support.